PENGARUH KEJUTAN BUDAYA ASING (CULTURE SHOCK) TERHADAP PERILAKU DAN KINERJA KARYAWAN BANK WOORI SAUDARA WILAYAH BOGOR - Dian Putri Indriani; Aida Vitayala Hubeis; Sadikin Kuswanto (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2021)
Bank Woori Saudara (BWS) is a merger between PT Bank Himpunan Saudara and Bank Woori Indonesia which brought togather two different cultures that are Indonesian culture and South Korean culture. Cultural changes at BWS require employees to adapt to new culture. Ineffective adaptation lead to many employees chosing to resign from BWS. The purpose of this study was to analyze the influence of culture shock on employee behavior and employee performance at BWS Bogor. The type of this study is explanatory research with survey method using primary data. The research data were obtained through questionnaire using a likert measurement scale with score of 1 to 5 and then distributed to 37 respondents who had been selected using non-probability sampling techniques that are classified as census. And secondary data through the method of observation, interview and literature study. The research was conducted using descriptive analysis for characteristcs respondens and path coefficient between the research variables using SmartPLS 3.0 software. The results showed that there was a significant influence between culture shock on employee behavior and employee performance positively. This is means that employees behavior to resign from BWS are influenced by affective domain, which is lack of appreciation that given by BWS. And later found that employee behavior does not affect employee performance. Keywords: culture shock, employee behavior, employee performance, individual characteristic, PLS